Diseño de un manual de control de activos fijos para mejorar la Gestión Administrativa en el Sindicato de Choferes Profesionales de san Miguel de Bolívar en el año 2012 - Quintana Lara, Patricia Fernanda (2014)
The Union of Professional Drivers of San Miguel de Bolivar has a manual control of fixed assets, which creates a problem in the receipt of goods, our research aims to provide with alternative solutions to the problems that are generated in administrative area, many officials of the institution have been neglected and have not given adequate importance to the control of fixed assets. In this work we used research methods such as inductive and deductive method, historical - logical, descriptive, also the data collection techniques such as the survey, interview and direct observation which allowed to detect the fundamental aspects for the development of the thesis. The Administrative staff conducted interviews and surveys of managers, staff and members of the Union of Drivers Operating San Miguel, for information that helped develop the conclusions and recommendations which manifest, that the Union does not have a manual control of fixed assets, which has hindered obtaining quick and timely information for decision -making. The proposal is made and developed with information from Union, have proper procedures as required for proper and appropriate control of fixed assets which are supported through systematic designs that optimize resources in management, custody of assets. The manual will become an instrument for the control that will be used and procedures performed within the Union for convenient safekeeping of goods and improve administrative management, enabling timely decision making.